2021
DOI: 10.1155/2021/5583691
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Berberis integerrima Fruit Extract on Glycemic Control Parameters in Patients with Type 2 Diabetes Mellitus: A Randomized Controlled Clinical Trial

Abstract: Background. Berberis integerrima Bunge fruits have been utilized in traditional medicine to control diabetes mellitus (DM). However, no clinical survey has been done in this regard. This study was conducted to clinically evaluate the effects of fruit extract of this plant in improving glycemic control indices in patients with type 2 DM (T2DM). Methods. In a randomized controlled clinical trial, patients with T2DM who met the inclusion criteria were randomly divided into two groups of drug (Berberis) and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Insulin sensitivity, activation of the AMPK pathway, induction of glucagon-like protein-1 secretion from the gut, stimulation of glycolytic processes in peripheral tissues, inhibition of gluconeogenesis, an increase in glucose transporters in cells, and a decrease in -glucosidase activity are just a few of the possible mechanisms underlying this effect. 17 The current investigation found that berberine had a significant effect on FPG serum levels, in accordance with the conclusions of this study of Homeira Rashidi, et al, 2018, 18 LadanTahmaseb, et al, 2019, 19 and Rasool Soltani, et al, 2021, discovered that patients with T2DM, had significant improvements than the control group, which is consistent with our findings. 20 Berberine has a protective impact on the kidneys, and that it is also through administration provided morphological and functional protection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Insulin sensitivity, activation of the AMPK pathway, induction of glucagon-like protein-1 secretion from the gut, stimulation of glycolytic processes in peripheral tissues, inhibition of gluconeogenesis, an increase in glucose transporters in cells, and a decrease in -glucosidase activity are just a few of the possible mechanisms underlying this effect. 17 The current investigation found that berberine had a significant effect on FPG serum levels, in accordance with the conclusions of this study of Homeira Rashidi, et al, 2018, 18 LadanTahmaseb, et al, 2019, 19 and Rasool Soltani, et al, 2021, discovered that patients with T2DM, had significant improvements than the control group, which is consistent with our findings. 20 Berberine has a protective impact on the kidneys, and that it is also through administration provided morphological and functional protection.…”
Section: Discussionsupporting
confidence: 92%
“…17 The current investigation found that berberine had a significant effect on FPG serum levels, in accordance with the conclusions of this study of Homeira Rashidi, et al, 2018, 18 LadanTahmaseb, et al, 2019, 19 and Rasool Soltani, et al, 2021, discovered that patients with T2DM, had significant improvements than the control group, which is consistent with our findings. 20 Berberine has a protective impact on the kidneys, and that it is also through administration provided morphological and functional protection. Apoptosis and oxidative stress were avoided in renal injury due to Ischemia-reperfusion (I/R) by administering berberine.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a randomized clinical trial (RCT) showed that intervention using the fruits of Berberis integerrima for 8 weeks decreased FBG and HbA1c in 65 T2D patients. 97 Another intervention involving Berberis vulgaris fruit for 8 weeks also decreased FBG. 98 Additionally, based on an RCT, it was shown that Morinda citrifolia fruit juice decreased FBG, HbA1c, and high sensitivity C-reactive protein (hs-CRP), and increased C-peptide in 20 T2D patients undergoing standard treatment, indicating that it could ameliorate diabetes by promoting insulin excretion and alleviating inflammation.…”
Section: Clinical Trialsmentioning
confidence: 98%
“…For the purpose of standardizing the barberry root extract, the polyphenol content was determined according to Folin-Ciocalteu's method as described before. 22 Briefly, 20 μL of the diluted solution were mixed with 100 μL of Folin-Ciocalteau reagent, 450 μL of water, and made up to 2 mL with saturated sodium carbonate solution. The solution was left for 2 h at room temperature and in a dark environment.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%